1999
DOI: 10.1103/revmodphys.71.1411
|View full text |Cite
|
Sign up to set email alerts
|

Light-meson spectroscopy

Abstract: We survey the current status of light meson spectroscopy. We begin with a general introduction to meson spectroscopy and and its importance in understanding the physical states of Quantum Chromo Dynamics (QCD). Phemenological models of hadron spectroscopy are described with particular emphasis on the constituent quark model and the qualitative features it predicts for the meson spectrum. We next discuss expectations for hadrons lying outside the quark model, such as hadron states with excited gluonic degrees o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
213
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(223 citation statements)
references
References 385 publications
10
213
0
Order By: Relevance
“…[29,30,31]). It has been suggested that the light scalars below or near 1 GeVthe isoscalars f 0 (600) (or σ), f 0 (980), the isodoublet K * 0 (800) (or κ) and the isovector a 0 (980)-form an SU(3) flavor nonet, while scalar mesons above 1 GeV, namely, f 0 (1370), a 0 (1450), K * 0 (1430) and f 0 (1500)/f 0 (1710), form another nonet.…”
Section: Quark Structure Of F 0 (980) and Input Parametersmentioning
confidence: 99%
“…[29,30,31]). It has been suggested that the light scalars below or near 1 GeVthe isoscalars f 0 (600) (or σ), f 0 (980), the isodoublet K * 0 (800) (or κ) and the isovector a 0 (980)-form an SU(3) flavor nonet, while scalar mesons above 1 GeV, namely, f 0 (1370), a 0 (1450), K * 0 (1430) and f 0 (1500)/f 0 (1710), form another nonet.…”
Section: Quark Structure Of F 0 (980) and Input Parametersmentioning
confidence: 99%
“…they can be constituents of molecular states with total widths of a few hundred MeV. The possibility has also been discussed elsewhere [17]. In this work, we investigate whether the present data on π 1 (1400) and π 1 (1600) support this specific molecular hypothesis.…”
Section: Introductionmentioning
confidence: 64%
“…These states have a fundamental role for the understanding of strong interaction since they are sensitive to chiral symmetry breaking and vacuum condensate effects. In addition, they allow us to probe the strong force at large distances where linear qq potential leading to confinement is expected to arise as indicated by Lattice QCD calculations [5].…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%